Factors Influencing Sanitation Management in Slums on The Riverbank of Kotalama Urban Village - Diana Putri Wijayanti; Fauzul Rizal Sutikno; Surjono Surjono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
One of the largest slum areas is located in Malang's Kotalama sub-district, which is distinguished by a considerable area that has undergone development along the riverbanks. The main challenge encountered in the area which has undergone development along the riverbanks, pertains to the insufficient management of sanitation. The aim of this research is to identify the sanitation conditions in the slum settlements within Kotalama sub-district and analyze the driving and inhibiting factors influencing sanitation management efforts in these slum settlements. The research method used is qualitative research. The results of the study concluded that 1) sanitation conditions in Kotalama District were in the "moderate" category with a score of 41.1. 2) The regulatory aspect reveals that the availability of policies serves as a driving factor, whereas the control and content of policies act as inhibiting factors. In the bureaucratic structure aspect, the presence of Micro SOPs serves as a driving force, while the availability of micro SOPs and fragmentation act as inhibiting factors. The resources aspect, encompassing human, budgetary, and infrastructural components, functions both as a driving and inhibiting factor. the communication aspect, effective communication among implementers and between implementers and the community is a driving and inhibiting factor. The Environmental aspects, including social conditions, community support, physical environment, and technology, have a dual role as both driving and inhibiting factors. The institutional aspects, such as capacity and government support, manifest as inhibiting factors. Furthermore, in the spatial aspect, both driving and inhibiting factors influence sanitation management in the Kotalama sub-district.